2018
DOI: 10.24200/sci.2018.20110
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of a PIN Diode RF Switch for Re configurable Antenna Application

Abstract: The paper proffers the procedure to model a PIN diode RF switch using full-wave EM solver, HFSS and utilizes the switch to built a simple partial ground plane antenna with omnidirectional radiation pattern. The proposed antenna has ability to tune it from ultra-wideband to narrowband mode. The frequency reconfigurability is accomplished by incorporating a rectangular slot resonator and a PIN diode RF switch embedded in the partial ground plane. The antenna demonstrates -10 dB impedance bandwidth from 500 MHz t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Nevertheless, these technologies may add an extra complexity to the antenna designs 3 . Also, it is observed that most of the proposed antenna show an acceptable SAR value to make it qualified to the portable applications in comparison to the proposed work in Kumar et al 28 However, the proposed study in Su et al 27 discussed the possibility of reconfiguration for the frequency band variation from UWB to narrow band, while, in this work, the proposed antenna is mainly designed for radiation pattern reconfiguration that is not discussed in Su et al 27 At the end, the proposed antenna is very suitable for the IoT applications where antennas for IoT technology must be miniaturized and printed on one side of the PCB boards to print the related electronic circuit on the other side of the substrate 29 …”
Section: Measurements and Results Validationsmentioning
confidence: 88%
“…Nevertheless, these technologies may add an extra complexity to the antenna designs 3 . Also, it is observed that most of the proposed antenna show an acceptable SAR value to make it qualified to the portable applications in comparison to the proposed work in Kumar et al 28 However, the proposed study in Su et al 27 discussed the possibility of reconfiguration for the frequency band variation from UWB to narrow band, while, in this work, the proposed antenna is mainly designed for radiation pattern reconfiguration that is not discussed in Su et al 27 At the end, the proposed antenna is very suitable for the IoT applications where antennas for IoT technology must be miniaturized and printed on one side of the PCB boards to print the related electronic circuit on the other side of the substrate 29 …”
Section: Measurements and Results Validationsmentioning
confidence: 88%
“…According to the IEEE C95.3, 2002 safety recommendations [27], the average SAR for 1 g of human tissue must be less than 1.6 W/kg. The study conducted in this paper was performed at a distance of 10 mm on body phantom of 50×57×21 mm 3 [28]. As shown in Figure 13, the designed antenna can operate safely up to an input power of 29 mW at 3.34 GHz where the max SAR is 1.562 W/Kg.…”
Section: Specific Absorption Rate Evaluationmentioning
confidence: 99%
“…So, the inductance of the parallel RLC resonant antenna circuit model is increased, and the resonant frequency of the circuit model is decreased. Thus, the microstrip antenna is further miniaturized [12,14,15]. 1.…”
Section: Design Of Slots and Csrr Loaded Mhmsa (S-csrr-mhmsa)mentioning
confidence: 99%